The Influence Of Competence On Personnel Performance: Mediating Role Of Organizational Citizenship Behavior - Rudi (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the determinants of personnel performance within the Medical and Health Division or Biddokkes of the Southeast Sulawesi Regional Police by examining the influence of competence and professionalism while evaluating the mediating role of Organizational Citizenship Behavior or OCB. Employing a quantitative approach involving 80 medical personnel as respondents, this research seeks to dissect work dynamics within a semi military system requiring high discipline and mental physical readiness. The statistical analysis results provide empirical evidence that competence has a positive and significant impact on personnel performance and serves as a very strong primary predictor in shaping OCB. Interesting findings indicate that although professionalism partially has no significant direct effect on performance, this variable proves to function effectively as a moderator strengthening relationships in the model. Specifically, the interaction between professionalism and OCB is able to have a tangible impact on improving personnel performance, indicating that professional attitude acts as an enhancer for extra role behavior. The conclusion of this study emphasizes that achieving optimal performance in the police environment requires synergy between technical competence improvement and the strengthening of OCB supported by mature professionalism as a catalyst for organizational success.